TEKNIK BIMBINGAN KONSELING ISLAM DAN REBT DALAM MENANGGULANGI PERILAKU MASKULINITAS WANITA - Zinatir Rahila; Mohamat Hadori; Asnawi (Fakultas Dakwah Universitas Ibrahimy, 2020)
Islamic guidance counseling is a process of assistance that is given periodically continuously (continuous) in order to deal with problems and increase religious awareness, so as to be able to provide high motivation and enthusiasm for life. Islamic boarding schools with students with different backgrounds must have different behaviors in carrying out the process of studying at pesantren. In this difference, there are female students who behave masculine, this behavior can cause negative things in the pesantren environment if there is no treatment. In this regard, action research is conducted using the REBT approach using Islamic guidance and counseling to address masculine behavior. The results show that the factors that shape masculine behavior in a female santri are psychological factors and environmental factors. Masculine behavior carried out including; wearing men's clothes, how to walk like a man, and in terms of sexuality related to the same sex. And the results of actions in cycles one and two indicate a change.